Evaluation of growth of Chlorella ellipsoidea in different culture media (International Journal of Agricultural Research, Innovation and Technology, 2015)
An experiment was conducted to evaluate the growth of Chlorella ellipsoidea in three different media viz,. medium I (pulse bran), medium II (soil extract) and medium III (inorganic) under the natural environmental conditions. The alga, C. ellipsoidea, reached maximum cell density of 56.32 × 106 cells ml-1 in 10 days in medium I (pulse bran), maximum cell density of 102.99 × 106 cells ml-1 in 11 days in medium II (soil extract) and maximum cell density of 64.23 × 106 cells ml-1 in 12 days in medium III (inorganic medium). The ranges of water temperature, air temperature and light intensity were 22 to 32ºC, 22 to 34ºC and 2.11 to 4.31 (× 103) lux, respectively during the culture period. The average sunshine period was 7.65 ± 1.57 hours. Total alkalinity, free CO2, pH, NO3-N, PO4- P of algal culture medium I, medium II and medium III were 220, 200 and 150 mg L-1 ; 26, 9 and 19 mg L-1; 7.9, 7.6 and 7.5; 45, 45 and 133.33 mg L-1; 10.9, 15.1 and 37.06 mg L-1, respectively. Cell densities of cultures of C. ellipsoidea under three treatments I, II and III, it can be concluded that cell densities under 3 treatments are significantly different (F=39.78) and treatment II (soil extract medium) is the best for algal (C. ellipsoidea) culture among three treatments. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22636 Int. J. Agril. Res. Innov. & Tech. 4 (2): 6-10, December, 2014